2020
DOI: 10.1002/mar.21329
|View full text |Cite
|
Sign up to set email alerts
|

When distraction may be a good thing: The role of distraction in low‐fit brand extension evaluation

Abstract: This study examines the effect of distraction after being exposed to information on low‐fit brand extension evaluation. We show that when consumers are distracted (vs. engaging in deliberate thinking) after encoding extension information they evaluate low‐fit brand extensions more favorably. Findings suggest that distraction can help establish connections of remotely associated information between a parent brand and a low‐fit extension. We also find that the effect of distraction is contingent on the individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…Table 2 implies that (1) short and frequent interruptions later in the decision process increase overall evaluations and purchase intentions for single products, and (2) one early interruption has a similar effect. These results may explain why interruptions can enhance consumers' product evaluations, as previously reported (Kupor et al, 2018;Kupor & Tormala, 2015;Liu, 2008;Nelson et al, 2009;Nowlis & Shiv, 2005;Zane et al, 2020;Zhang et al, 2020).…”
Section: Connection To Earlier Worksupporting
confidence: 75%
See 1 more Smart Citation
“…Table 2 implies that (1) short and frequent interruptions later in the decision process increase overall evaluations and purchase intentions for single products, and (2) one early interruption has a similar effect. These results may explain why interruptions can enhance consumers' product evaluations, as previously reported (Kupor et al, 2018;Kupor & Tormala, 2015;Liu, 2008;Nelson et al, 2009;Nowlis & Shiv, 2005;Zane et al, 2020;Zhang et al, 2020).…”
Section: Connection To Earlier Worksupporting
confidence: 75%
“…In contrast, post‐deliberate‐thinking distractions encourage rule‐based learning, increasing persuasion, enhancing TV‐watching experiences, and delighting customers (Kupor & Tormala, 2015; Nelson et al, 2009; Nowlis & Shiv, 2005). Due to their temporal structure, later interruptions can reduce perceived risk, encourage risk‐taking behavior, trigger associations between parent brands and their extensions, and enhance evaluations of ill‐fitting brand extensions (Kupor et al, 2018; Zhang et al, 2020).…”
Section: Research Hypothesesmentioning
confidence: 99%
“…For example, Parker et al (2017) has provided insights into the suitable time of launching a brand’s first far extension product category. Zheng et al (2019) and Zhang et al (2020) have revealed the positive effect of distraction and the product display format on low fit extension evaluation.…”
Section: Introductionmentioning
confidence: 98%
“…Even though the importance of near category extension with the brands has been widely underlined in the literature, there are certainly numerous examples of enterprises that have introduced distant extension products in the real market, both successfully and unsuccessfully. As such, recent studies have attempted to resolve how to improve consumer’s acceptance of low fit extension products ( Parker et al, 2017 ; Shang et al, 2017 ; Zhang et al, 2020 ). For example, Parker et al (2017) has provided insights into the suitable time of launching a brand’s first far extension product category.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies used messages (e.g. announcing when or where an extension shall be launched), rather than ad appeals, to experimentally manipulate consumers' perception of low-fit extensions (Kim and Park, 2019;Zhang et al, 2020). Such experimental priming messages differ from ad appeals, in that ad appeal is the approach to communicate a message via advertising (Belch and Belch, 2004;Dix and Marchegiani, 2013).…”
Section: Introductionmentioning
confidence: 99%